Changing perspectives in extension management - C.R. Desai, (Journal of Agricultural Extension Management, 2025)
Management of Agricultural Extension as a key activity has been in formal practice since the last five decades in India. During this period it has passed through various stages of transformation depending upon the requirement of the situation, the personnel managing the systems, the policy makers and their understanding, the programme planners and their capacity to understand, the implementers of the projects and programmes apart from the demands of the farming community